An unusual cause of dysphagia: "DISHphagia". (April 2015) - Bacigaluppi, S.; Merciadri, P.; Secci, F.; Bragazzi, N. L.; Zona, G.
Abstract Progressive dysphagia and dyspnoea presenting after major neck trauma can occasionally be secondary to post-traumatic inflammation and mass effect associated with a calcified osteophytic anterior longitudinal ligament, a frequent finding in diffuse idiopathic skeletal hyperostosis, though rarely enough to cause such symptoms. In these circumstances, surgical decompression may prove effective.